Analisis Diagram T-S Berdasarkan Parameter Oseanografis di Perairan Selat Lombok - Harvianto, Loecky; Parengkuan, Maxi; Koropitan, Alan F.; Agustiadi, Teguh (Surya Octagon Interdisciplinary Journal of Science and Technology, 2015)
Research of water masses by using conductivity temperature depth are conducted in the Lombok Strait during September 2014 under the Cruise SITE Leg II to Lombok Strait. The aim of the research is to investigate Temperature-Salinity Diagram based on oceanographic parameters in Lombok Strait. Temperature-Salinity Diagram shows the origin of the water masses across Lombok Strait. The results of this research shows water masses across Lombok Strait comes from North Pacific Subtropical Water (NPSW) on ~ 150 m depth and North Pacific Intermediate Water (NPIW) on ~ 400 m depth. The differences values of salinity reference and salinity measurement indicates the properties of NPSW and NPIW are dynamic, verified by the number of salinity reference is 34,55 Psu on ~ 150 m depth, whereas the salinity number of five station in order are  34,63 Psu; 34,65 Psu; 34,65 Psu; 34,57 Psu; 34,52 Psu. The difference of salinity number caused by strong vertical mixing in Indonesian waters.